Structural and Functional Dysbiosis of Fecal Microbiota in Chinese Patients With Alzheimer's Disease - Ling, Zongxin; Zhu, Manlian; Yan, Xiumei; Cheng, Yiwen; Shao, Li; Liu, Xia; Jiang, Ruilai; Wu, Shaochang (Frontiers in Cell and Developmental Biology, 2021)
Increasing evidence suggests that gut dysbiosis plays vital roles in a variety of gut–brain disorders, such as Alzheimer’s disease (AD). However, alterations of the gut microbiota as well as their correlations with cognitive scores and host immunity have remained unclear in well-controlled trials on Chinese AD patients. In this study, samples from 100 AD patients, and 71 age- and gender-matched, cognitively normal controls were obtained to explore the structural and functional alterations of the fecal microbiota targeting the V3–V4 region of the 16S rRNA gene by MiSeq sequencing, and to analyze their associations with clinical characteristics. Our data demonstrated a remarkably reduction in the bacterial diversity and alterations in the taxonomic composition of the fecal microbiota of the AD patients. Interestingly, the abundant butyrate-producing genera such as Faecalibacterium decreased significantly, where this was positively correlated with such clinical indicators as the MMSE, WAIS, and Barthel scores in the AD patients. On the contrary, abundant lactate-producing genera, such as Bifidobacterium, increased prominently, and were inversely correlated with these indicators. This shift in the gut dysbiosis of the microbiota, from being butyrate producers to lactate producers, contributed to immune disturbances in the host that could be used as non-invasive biomarkers to distinguish the controls from the AD patients. Moreover, several predicted functional modules, including the biosynthesis and the metabolism of fatty acids, that were altered in the microbiota of the AD patients could be utilized by the bacteria to produce immunomodulatory metabolites. Our study established the structural and functional dysbiosis of fecal microbiota in AD patients, and the results suggest the potential for use of gut bacteria for the early, non-invasive diagnosis of AD, personalized treatment, and the development of tailor-made probiotics designed for Chinese AD patients.